Relationship Between Mental Health and Foot Pain. Issue 8 (August 2014) - Butterworth, Paul A.; Urquhart, Donna M.; Cicuttini, Flavia M.; Menz, Hylton B.; Strauss, Boyd J.; Proietto, Joseph; Dixon, John B.; Jones, Graeme; Wluka, Anita E.
<x xml:space="preserve">Abstract</x> Objective Although mental health is related to the persistence of musculoskeletal pain, our understanding of the relationship between mental health and foot pain is limited. Subsequently, we conducted a 3‐year longitudinal study to examine the relationship between mental health and foot pain in a community‐based population. Methods Eighty‐three community‐dwelling participants (mean ± SD body mass index [BMI] 35.3 ± 9.0 kg/m2) who had foot pain at study inception in 2008 and for whom measures of mental health (Short Form 36 [SF‐36] health survey mental component summary [MCS]) were available, were invited to take part in this followup study in 2011. Change in foot pain was determined by the difference between the Manchester Foot Pain and Disability Index score at baseline and followup; therefore, a decrease in the score indicated improved foot pain and an increase indicated deterioration in foot pain. Linear regression was used to determine the factors affecting change in foot pain. Results Of the 62 respondents (75% response rate, 49 women and 13 men), there were 27 (44%) whose foot pain deteriorated. A higher MCS score of the SF‐36 health survey at baseline was associated with a slower progression of foot pain (β coefficient −0.29, 95% confidence interval −0.42, −0.01), adjusted for age, sex, BMI, and physical health. Conclusion Mental health is associated with changes in foot pain. Clinicians dealing with this population should consider the contribution of mental health in their management and treatment of foot pain.